2022
DOI: 10.1101/2022.03.29.22273093
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Severe outcomes in unvaccinated COVID-19 cases <18 years during different variant waves in Norway

Abstract: Objectives We used linked individual-level data from national registries to compare the risk of severe outcomes among unvaccinated COVID-19 cases <18 years between waves of the SARS-CoV-2 Alpha, Delta and Omicron variants in Norway. Methods Our outcomes were hospitalisation with acute COVID-19 or multisystem inflammatory syndrome in children (MIS-C). We calculated adjusted risk ratios (aRR) with 95% confidence intervals (CIs) using multivariable log-binomial regression, adjusting for variant wave, demograp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…A large study performed in Europe showed a 2.50-fold increase in adjusted risk for hospitalization during the Alpha wave, along with a more modest 1.32-fold increase in this adjusted risk during Delta wave, when compared to Omicron. 20 The authors of the European study postulate that the lower risk of hospitalization with the later waves may have been secondary to increased vaccination rates in the pediatric population. Here, we also show that pediatric patients were more likely to be admitted to the hospital during the pre-Delta and Delta waves (Adjusted ORs of 2.51 and 2.07, respectively) as compared to Omicron.…”
Section: Discussionmentioning
confidence: 99%
“…A large study performed in Europe showed a 2.50-fold increase in adjusted risk for hospitalization during the Alpha wave, along with a more modest 1.32-fold increase in this adjusted risk during Delta wave, when compared to Omicron. 20 The authors of the European study postulate that the lower risk of hospitalization with the later waves may have been secondary to increased vaccination rates in the pediatric population. Here, we also show that pediatric patients were more likely to be admitted to the hospital during the pre-Delta and Delta waves (Adjusted ORs of 2.51 and 2.07, respectively) as compared to Omicron.…”
Section: Discussionmentioning
confidence: 99%
“…With the recent emergence of the more transmissible Omicron variant, recent studies suggest an even lower risk of PIMS-TS ( 54 , 55 ). Prior infection and higher vaccine uptake in adolescents will likely have contributed to this lower risk.…”
Section: Discussionmentioning
confidence: 99%